The impact of ICT adoption and trade openness on youth unemployment in ASEAN: opportunity or challenge? - Prabowo, Tripitono Adi; Prasetyo, Alvin Sugeng; Wahyuningsih, Diah (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
This study investigates the long-term impact of Information and Communication Technology (ICT) adoption and trade openness on youth unemployment in ASEAN countries over the period 2000–2023. Panel data are analyzed using the Fully Modified Ordinary Least Squares (FMOLS) estimation method. The empirical results indicate that trade openness reduces youth unemployment, particularly among male youth. However, its effect is relatively weaker and not consistently significant for female youth, suggesting the presence of gender disparities in labor absorption within tradable sectors. Furthermore, digital infrastructure plays a crucial role in mitigating youth unemployment. Both fixed broadband and mobile cellular subscriptions are found to significantly reduce youth unemployment rates, with broadband access exhibiting a stronger and more consistent effect across models. Overall, the findings suggest that ICT adoption and trade openness constitute important mechanisms for reducing youth unemployment in ASEAN countries.